2021
DOI: 10.1021/acsami.1c10717
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors Based on Solid-Phase Molecular Self-Assembly: Moisture-Strain Dual Responsiveness Facilitated Extremely High and Damage-Resistant Sensitivity

Abstract: Wearable sensing technologies have gained increasing interest in biomedical fields because they are convenient and could efficiently monitor health conditions by detecting various physiological signals in real time. However, common film sensors often neglect body moisture and enhance the sensitivity by enhancing the conductive dopants and self-healing ability. We report in this work a supramolecular film sensor based on solid-phase molecular self-assembly (SPMSA), which smartly utilizes the body moisture to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Recently, Yan et al found that molecules in the precipitates formed with the aqueous mixture of ionic surfactant and oppositely charged polyelectrolyte may undergo self-assembly to form large-area self-supporting films under pressure in the presence of a tiny amount of water. The driving forces for the multiscale self-assembly process are mainly the hydrophobic interaction between surfactant molecules. The electrostatic interaction between the polyelectrolyte chain and surfactant molecules is to endow the film with the self-supporting ability through the cross-linking of nanodomains formed by surfactants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Yan et al found that molecules in the precipitates formed with the aqueous mixture of ionic surfactant and oppositely charged polyelectrolyte may undergo self-assembly to form large-area self-supporting films under pressure in the presence of a tiny amount of water. The driving forces for the multiscale self-assembly process are mainly the hydrophobic interaction between surfactant molecules. The electrostatic interaction between the polyelectrolyte chain and surfactant molecules is to endow the film with the self-supporting ability through the cross-linking of nanodomains formed by surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…However, so far most molecular self-assemblies are obtained in the form of solution-based colloidal dispersions. This solution-based molecular self-assembly is hard to work with when bulk macroscopic materials are required . To tackle this problem, we recently developed a strategy of solid-phase molecular self-assembly (SPMSA), with which supramolecular films can be obtained at large scales . This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular self-assembled materials but also makes it possible to achieve diversified functions. ,, …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations